2002
DOI: 10.1152/ajpgi.00297.2001
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal NaCl transport in NHE2 and NHE3 knockout mice

Abstract: Sodium/proton exchangers [Na(+)/H(+) (NHEs)] play an important role in salt and water absorption from the intestinal tract. To investigate the contribution of the apical membrane NHEs, NHE2 and NHE3, to electroneutral NaCl absorption, we measured radioisotopic Na(+) and Cl(-) flux across isolated jejuna from wild-type [NHE(+)], NHE2 knockout [NHE2(-)], and NHE3 knockout [NHE3(-)] mice. Under basal conditions, NHE(+) and NHE2(-) jejuna had similar rates of net Na(+) (approximately 6 microeq/cm(2) x h) and Cl(-)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
148
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(158 citation statements)
references
References 52 publications
10
148
0
Order By: Relevance
“…In addition the presence of NHE2 and NHE3 on the apical membrane of colonic epithelial cells has been confirmed [20]. NHE3 knock out mice develope diarrhoea, which supports the idea that this might be the dominant NHE isoform, responsible for Na + uptake in the intestine [12,35,49]. Together with NHE3, the SLC26A3 Cl -/HCO 3 -exchanger (or downregulated in adenoma; DRA), a member of the SLC26 gene family, maintains the absorption of NaCl in the colon.…”
Section: Discussionsupporting
confidence: 56%
“…In addition the presence of NHE2 and NHE3 on the apical membrane of colonic epithelial cells has been confirmed [20]. NHE3 knock out mice develope diarrhoea, which supports the idea that this might be the dominant NHE isoform, responsible for Na + uptake in the intestine [12,35,49]. Together with NHE3, the SLC26A3 Cl -/HCO 3 -exchanger (or downregulated in adenoma; DRA), a member of the SLC26 gene family, maintains the absorption of NaCl in the colon.…”
Section: Discussionsupporting
confidence: 56%
“…Interferon-γ and TNF-α decrease NHE3 activity causing diarrhea [51,145,2]. Consistent with a role in inflammatory bowel disease, NHE3 expression and/or activity is decreased in mouse models and human disease [159,187] .…”
Section: Slc9a3 -Nhe3mentioning
confidence: 67%
“…Ultimately, despite significant expression and activity in both bowel and kidney, it appears that the absence of NHE2 can be compensated for. It is likely that NHE3 and NHE8 perform these compensatory roles, at least under some circumstances [6,51,69]. Perhaps not surprising, given the relatively benign phenotype for NHE2 KO mice, there is no known human disease ascribed to defects in this transporter [110].…”
Section: Slc9a2 -Nhe2mentioning
confidence: 99%
“…45 Indeed, NHE3-knockout mice show lower BP compared with wildtype mice. 46 Thus, blockade of intestinal NHE3 to reduce intestinal sodium absorption could be a potentially novel strategy for treatment of hypertension 47 as is the case with commonly used diuretics which block renal tubular reabsorption of sodium. Animal studies have shown that by inhibiting intestinal NHE3-mediated sodium absorption, SAR218034 can serve as a new class of antihypertensive drugs.…”
Section: Sodium Absorption From the Intestinementioning
confidence: 99%